Studies on Schismatoglottideae (Araceae) of Peninsular Malaysia III: New species for the Schismatoglottis Calyptrata Clade - Wong, Sin Yeng; Boyce, Peter C.; Hoe, Yin Chen (Firenze University Press, 2021)
/ree new colonial species of Schismatoglottis Calyptrata clade are described from Peninsular Malaysia and compared with the four already known morphologically similar species described from there. All seven species are illustrated from living plants and an identi1cation key is provided.